Mitigation of Unbalance Voltages for Islanded Micro-Grids by using Five Level Diode Clamped Multilevel Inverter - Dr. B.Mouli Chandra; Dr. B.Venkata Prasanth; Komati LakshmiPrasanna.; Sri. T. Srinivas (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
— In this paper, a control strategy for paralleled three-phase inverters is proposed. The proposed local controller includes inner loop controller and droop controller and virtual impedance and unbalance compensator. The voltage/current controllers are to better mitigate voltage distortion when supplying non linear loads. Linear and non liner loads are to accurate current sharing for droop controller and virtual impedance. According to the amplitude of the negative sequence voltage by adjusting voltage reference. Compensation signal is sent to the DGs local controller, unbalance factor is reduced significantly. Unbalance is caused by single phase generators. It can be mitigated to an extremely low. In order to proposed control strategy for ac micro-grid consist of three three phase three leg inverters